2014
DOI: 10.3354/dao02771
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of three virulence-associated TonB-dependent outer membrane receptors of Pseudomonas fluorescens

Abstract: Pseudomonas fluorescens is a Gram-negative bacterium that can infect a wide range of farmed fish. However, very little is known about the virulence mechanism of P. fluorescens as a fish pathogen. In this study, we identified and analyzed 3 TonB-dependent outer membrane receptors (TDRs) from a pathogenic P. fluorescens strain isolated from fish. In silico analysis revealed that all 3 proteins (named Tdr1 to 3) possess structural domains typical of TDRs. Quantitative real time RT-PCR analysis showed that tdr1, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…2016). In Pseudomonas fluorescens , these TonB receptors were upregulated under iron‐limiting conditions and TonB proteins are also being investigated in potential subunit vaccine candidates (Zhang et al., 2014). In the current study, the TBomr1 expression was found to be decreased in the B.17 strain at 96‐hr post‐iron‐limiting media exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2016). In Pseudomonas fluorescens , these TonB receptors were upregulated under iron‐limiting conditions and TonB proteins are also being investigated in potential subunit vaccine candidates (Zhang et al., 2014). In the current study, the TBomr1 expression was found to be decreased in the B.17 strain at 96‐hr post‐iron‐limiting media exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains that overproduce siderophores may be considered hypervirulent, and these siderophores can serve as toxins and immunomodulators (Holden & Bachman, 2015). Siderophores with attached iron are brought into the bacterial cell via outer membrane receptors (OMRs; Andrews et al., 2003; Zhang et al., 2014). The energy required to move this sequestered iron into the bacterial cell is provided by the TonB protein system, and it has been found that all Gram‐negative bacteria have at least one TonB protein (Beddek et al., 2004; Chu et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, catfish experiments demonstrated a 2.16-fold reduction in Ei Δ tonB virulence compared with wild-type E. ictaluri . Similarly, P. fluorescens mutants defective in the TonB-dependent outer membrane receptor (TDRs) tdr1, tdr2, and tdr3, which had 26.7, 22.3, and 24.5% mean percent mortalities, respectively, compared with 70% mortality caused by the parent strain in a turbot ( Seophthalmus maximus ) model fish (Zhang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of Pf Fha in TSS fha was confirmed by PCR analysis. In addition, single-copy plasmid insertion in TSS fha was further confirmed by the quantitative real-time PCR (qRT-PCR) method described previously (Zhang et al, 2014). …”
Section: Methodsmentioning
confidence: 99%